The Role of Fintech Lending in Financial Inclusion and Poverty Alleviation: A Systematic Review - Thomas Airlangga; Yos Sunitiyoso; Oktofa Yudha Sudrajad (Research Synergy Foundation, 2025)
Fintech lending has emerged as a transformative tool for expanding financial inclusion and reducing poverty. This study conducts a systematic literature review (SLR) of 39 articles published between 2010 and 2023, using Scopus as the primary database, to evaluate the impact of fintech lending on poverty alleviation across different socio-economic contexts. The findings reveal that fintech lending enhances financial accessibility through mobile money, digital microfinance, and alternative credit-scoring mechanisms, particularly benefiting underserved populations. However, challenges such as the digital divide, financial literacy gaps, and risks of over-indebtedness persist. Islamic finance models, including digital zakat and Shariah-compliant microfinance, have shown the potential to support poverty alleviation in Muslim-majority regions. Effective fintech implementation depends on adaptive regulatory frameworks, consumer protection measures and integration with traditional financial institutions. This study contributes to the literature by synthesizing global insights on fintech’s role in poverty alleviation and identifying key success factors for sustainable financial inclusion. Policymakers and practitioners can leverage these findings to develop inclusive fintech ecosystems that mitigate risks while maximizing social and economic impact. Future research should explore the long-term effects of fintech lending and its role in environmental sustainability and regulatory advancements.